Continuing recovery of wolves in Europe - Di Bernardi, Cecilia; Chapron, Guillaume; Kaczensky, Petra; Álvares, Francisco; Andrén, Henrik; Balys, Vaidas; Blanco, Juan Carlos; Chiriac, Silviu; Ćirović, Duško; Drouet-Hoguet, Nolwenn; Huber, Djuro; Iliopoulos, Yorgos; et al. (PLOS Sustainability and Transformation, 2025)
The recovery of wolves ( Canis lupus ) across Europe is a notable conservation success in a region with extensive human alteration of landscapes and high human population densities. We provide a comprehensive update on wolf populations in Europe, estimated at over 21,500 individuals by 2022, representing a 58% increase over the past decade. Despite the challenges of high human densities and significant land use for agriculture, industry, and urbanization, wolves have demonstrated remarkable adaptability and increasing population trends in most European countries. Improved monitoring techniques, although varying in quality and scope, have played a crucial role in tracking this recovery. Annually, wolves kill approximately 56,000 domestic animals in the EU, a risk unevenly distributed and differently handled across regions. Damage compensation costs 17 million EUR every year to European countries. Positive economic impacts from wolf presence, such as those related to reducing traffic accidents with wild ungulates or supporting wildlife tourism, remain under studied. Wolf recovery in Europe is supported by diverse policy and legal instruments such as LIFE programs, stakeholder platforms, as well as the EU Habitats Directive and the Bern Convention. Coexisting with newly established wolf populations in Europe entails managing impacts on human activities, including livestock depredation, competition for game, and fear of attacks on humans, amidst varying social and political views on wolf recovery. Sustainable coexistence continues to operate in evolving and complex social, economic, and political landscapes, often characterized by intense debates regarding wolf policies.